MARKETING ANALYSIS OF CASSAVA (Manihot esculenta) THROUGH SCP (Structure Conduct Performance) APPROACH IN BANDAR SUB-DISTRICT, SIMALUNGUN REGENCY - Hutasuhut, Septia Adinda; Jamil, Muhammad; Alham, Fiddini (Syarif Hidayatullah State Islamic University Jakarta, 2024)
This study aims to analyze the cassava marketing system through the SCP (Structure Conduct Performance) approach in Bandar District, Simalungun Regency. The location of the research was determined using the random sampling method. The sample in this study consisted of 37 farmers determined using the Slovin formula, 5 collectors and 5 retailers determined by snowball sampling. The data analysis methods used are qualitative (descriptive) and quantitative analysis. The results show that the results of the study show that the analysis of the market structure formed in the marketing of cassava in Bandar District, Simalungun Regency at the farmer level leads to a loose oligopoly market. Meanwhile, at the channel level, marketing institutions show a tight oligopoly market. Market behavior analysis on cassava has a low bargaining position so that farmers do not have the power to determine the price of cassava and only act as a price taker. The results of the market performance analysis showed two patterns of marketing channels, the marketing margin in channel I, the value of the marketing margin was Rp. 1,380/Kg and in the second marketing channel was Rp. 1,700/Kg. The value of the farmer's share in the first marketing channel was 54.00% and the value of the second marketing channel was 43.33%. The value of cassava marketing efficiency in marketing channel I is 14.00% and marketing channel II is 16.80%, both channels can be said to be efficient because the value is less than 50%.